Benign Histiocyte-Rich Pseudotumor Developing Postchemotherapy and Mimicking Residual Disease - Amrit P. Singh; Glenn P. Murray; Soumya Pandey (Hindawi Limited, 2020)
Histiocyte-rich pseudotumors (HRPT) developing postchemoradiation therapy are a florid response to treatment and reparative change. Although these are benign processes, clinically and radiologically, these may mimic recurrent/relapsed disease. We describe a case of an adult male with history of diffuse large B-cell lymphoma (DLBCL), status postchemoradiation therapy, who developed HRPT at the site of original involvement, mimicking relapse of disease on positron emission tomography/computed tomography (PET/CT) imaging. This is one of the few reported cases of posttreatment HRPT. This entity is important to point out the limitations of PET/CT imaging in patients with lymphomas and metastatic disease and stresses the importance of an excisional biopsy for determining relapse and the need for further treatment.